IMPROVING THE PHYSICO-CHEMICAL PROPERTIES OF UREA FURFURAL RESIN (American Journal of Pedagogical and Educational Research, 2023)
In article, in the formation of a film from a solution of synthetic resin, mochivena and melamine are synthesized using formaldehyde, epoxide, furfural, acrylate substances. Production of films made from resins obtained from melamine formaldehyde, phenol formaldehyde and mercury and studying their physical and chemical properties is of great importance. Despite the fact that the potential of the chemical industry of the republic has a high position in the world, the demand for the development of high-quality lacquers for furniture and the production of car enamels is increasing every year.In this article, in the formation of a film from a solution of synthetic resin, mochivena and melamine are synthesized using formaldehyde, epoxide, furfural, acrylate substances. Production of films made from resins obtained from melamine formaldehyde, phenol formaldehyde and mercury and studying their physical and chemical properties is of great importance. Despite the fact that the potential of the chemical industry of the republic has a high position in the world, the demand for the development of high-quality lacquers for furniture and the production of car enamels is increasing every year